Peculiarities of psychotherapy in the comprehensive treatment of depressive disorders in patients with brain tumors - Hnenna, Ольга; Ohorenko, Вікторія (Psychosomatic Medicine and General Practice, 2021)
Background. Depression is one of the most common mental illnesses in patients with brain tumors. The use of modern pharmacotherapy, providing appropriate psychotherapeutic care to cancer patients can prevent the development of psychopathological disorders, especially depressive states (due to the risk of suicidal behavior), and help shape behavioral strategies that will optimize the treatment and rehabilitation of patients. Aim of the research. To investigate the effectiveness of psychotherapeutic correction of depressive disorders in patients with brain tumors. Materials and methods. 250 patients with primary brain tumors were examined. A comprehensive clinical and psychodiagnostic examination of patients was conducted, which included objective data from available medical records and voluntary consent of patients. The following psychodiagnostic techniques were used as assessment tools: the psychopathological symptom severity questionnaire (SCL-90-R) and the Bekhter Institute personal questionnaire. Results and discussion. The revealed symptom complexes of psychopathological and pathopsychological characteristics of the patients' condition became the clinical substantiation of the choice of methods of psychotherapeutic correction. Adjuvant psychological therapy, individual, rational and family psychotherapy were used as the basic method of psychotherapeutic influence. Positive dynamics of changes in the structure of psychopathological symptoms was found in 130 patients (97.0%) as a result of psychotherapeutic effects. It was found that in most patients there was a decrease in melancholic-depressive and anxiety-depressive states, in 48 cases it was possible to achieve regression of phobic, hypochondriac, senestopathic and hypochondriac components; 29 patients showed positive dynamics of reduction of depressive disorders, which were combined with somatoform symptom complexes. Conclusion. The principles of organization of psychotherapeutic care for neurooncological patients should include not only an individual-personal approach, but also a family one. Adjuvant psychological therapy and other psychotherapeutic interventions in combination with psychopharmacotherapy can reduce the development of depressive disorders by 25-30%.